Evaluasi Penggunaan Obat Antihipertensi Pada Pasien Rawat Jalan di Rumah Sakit Setia Mitra Jakarta - Wulandari, Ainun; Arum, Fitria Diah; Febriani, Amelia (LPPM, INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2023)
The high number of people with high mobility raises the possibility of increased risk factors for hypertension. Hypertension ranks eighth out of the top ten diseases based on the highest number of patients in 2022 at Setia Mitra Hospital. Management of hypertension can be done using drugs. Drug use needs to be evaluated by assessing the rationality of drug use. Rational use of drugs is expected to increase the effectiveness of therapy, so that therapeutic goals are achieved and prevent disease complications. The aim of the study was to evaluate the use of antihypertensive drugs based on age, sex, blood pressure, drug combinations used, and rationality of drug use. The research was a descriptive study with retrospective data collection. The sampling technique was purposive sampling. The results of the research on outpatient hypertension characteristics at Setia Mitra Hospital were highest based on age, namely 56-65 years by 34% and gender, namely female patients by 70%. Blood pressure for the initial treatment was stage 2 hypertension at 62%, while the blood pressure for the final treatment was prehypertension by 54%. The distribution of the most prescribed drugs was single therapy at 40.1%. The rationality of using antihypertensive drugs based on the right patient was 94%, the right indication was 100%, the right drug was 90%, and the right dose was 96%. 90% of the use of antihypertensive drugs in outpatients at Setia Mitra Jakarta Hospital ffulfilsrationality based on the right patient, indication, drug, and dose.